Size-controllable synthesis of bare gold nanoparticles by femtosecond laser fragmentation in water. (20th January 2015) - Maximova, Ksenia; Aristov, Andrei; Sentis, Marc; Kabashin, Andrei V
Abstract: We report a size-controllable synthesis of stable aqueous solutions of ultrapure low-size-dispersed Au nanoparticles by methods of femtosecond laser fragmentation from preliminary formed colloids. Such approach makes possible the tuning of mean nanoparticle size between a few nm and several tens of nm under the size dispersion lower than 70% by varying the fluence of pumping radiation during the fragmentation procedure. The efficient size control is explained by 3D geometry of laser fragmentation by femtosecond laser-induced white light super-continuum and plasma-related phenomena. Despite the absence of any protective ligands, the nanoparticle solutions demonstrate exceptional stability due to electric repulsion effect associated with strong negative charging of formed nanoparticles. Stable aqueous solutions of bare gold nanoparticles present a unique object with a variety of potential applications in catalysis, surface-enhanced Raman spectroscopy, photovoltaics, biosensing and biomedicine.